2016
DOI: 10.1038/srep23093
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate fertilisation does not enhance CO2 responses in two tropical seagrass species

Abstract: Seagrasses are often considered “winners” of ocean acidification (OA); however, seagrass productivity responses to OA could be limited by nitrogen availability, since nitrogen-derived metabolites are required for carbon assimilation. We tested nitrogen uptake and assimilation, photosynthesis, growth, and carbon allocation responses of the tropical seagrasses Halodule uninervis and Thalassia hemprichii to OA scenarios (428, 734 and 1213 μatm pCO2) under two nutrients levels (0.3 and 1.9 μM NO3−). Net primary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The plant‐scale response to p CO 2 may have been constrained by the experimental duration (7 wk) (Palacios & Zimmerman, ). Carbon‐limited productivity has also been observed in a range of short‐term studies on seagrasses (Jiang et al ., ; Ow et al ., ) when productivity is not limited by other environmental conditions, including light and nutrient availability (Palacios & Zimmerman, ; Ow et al ., ,b). Therefore, future OA and relief from DIC limitation may lead to increases in seagrass productivity, growth, and biomass, enabling some species to become localized ‘winners’ ( sensu Fabricius et al ., ) when other environmental conditions do not limit the response (Hall‐Spencer et al ., ; Takahashi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plant‐scale response to p CO 2 may have been constrained by the experimental duration (7 wk) (Palacios & Zimmerman, ). Carbon‐limited productivity has also been observed in a range of short‐term studies on seagrasses (Jiang et al ., ; Ow et al ., ) when productivity is not limited by other environmental conditions, including light and nutrient availability (Palacios & Zimmerman, ; Ow et al ., ,b). Therefore, future OA and relief from DIC limitation may lead to increases in seagrass productivity, growth, and biomass, enabling some species to become localized ‘winners’ ( sensu Fabricius et al ., ) when other environmental conditions do not limit the response (Hall‐Spencer et al ., ; Takahashi et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Seagrass species vary in their preferred carbon substrates, which affects their response to increasing p CO 2 (Campbell & Fourqurean, ; Ow et al ., ). But in both species, an increased p CO 2 has previously led to higher productivity, leading to the conclusion that they were carbon limited (Uku et al ., ; Ow et al ., , ); and furthermore, both species thrive at CO 2 ‐enriched volcanic seeps (Takahashi et al ., ). There are a number of possible reasons why they did not respond to end‐of‐century p CO 2 in this study, including downregulation or acclimation (Smith & Dukes, ; Browman, ) after the longer exposure in this study compared with the previous experimental studies on the same species, which were 2–3 wk (Ow et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic activities could also affect the growth and metabolism shown by a study conducted by Karlina et al [64]. It concluded that anthropogenic activities such as tourism could lead to seagrass meadow degradation in the form of spatial distribution, percent coverage, biodiversity, and community structure of seagrass meadows [65]. This study found that anthropogenic activities at Sanur and Samuh have affected the population density represented by plant coverage.…”
Section: B Plant Biomass and Carbon Storagementioning
confidence: 57%
“…Most of the studies on the effects of elevated CO 2 levels on seagrasses have been on the responses of productivity and light requirements (Beer and Koch, 1996;Thom, 1996;Zimmerman et al, 1997;Palacios and Zimmerman, 2007), photosynthetic and leaf growth rates (Alexandre et al, 2012) and the uptake rate of ammonium and nitrate (Short and Neckles, 1999;Alexandre et al, 2012;Ow et al, 2016). Results so far have suggested that, seagrass meadows can utilize the increased CO 2 concentration from the water column and enhance their photosynthetic activity and community metabolism (Frankignoulle and Disteche, 1984;Frankignoulle and Bouquegneau, 1990;Invers et al, 2001).…”
Section: Introductionmentioning
confidence: 99%